Pemanfaatan Sosial Media Branding pada Mitra Anugrah Jaya untuk Meningkatkan Pemasaran Digital Aneka Keripik Extra Delicious - Weda Adistianaya Dewa; Indah Dwi Mumpuni; Linda Suvi` Rahmawati (Jurnal Pemberdayaan Masyarakat, 2022)
Social media is the right medium for marketing, developing content, posting products, asking for input, and others that can improve and keep their business from losing out in the midst of the existing competition. One of the business industries that will develop is Anugrah Jaya’s partner which is engaged in the food processing industry, namely Assorted Chips "Extra Delicious". This partner is owned by Shinta Niawati, located in Pandansari Lor Village, Jabung District, 17 km from the STMIK PPKIA Pradnya Paramita community service team, Malang. The conventional marketing pattern that is being carried out needs changes in the digital era in order to expand the product marketing network through social media branding, in addition to not understanding financial management in running its business and the Anugrah Jaya logo does not yet have business ownership recognition. The results of the activities carried out by the service team include providing training and assistance in the use of social media branding of various "Extra Delicious" chips so as to increase wider market segmentation, and financial management assistance so that financial management can run well. and assisting in the registration of Anugrah Jaya's business logo in order to obtain copyright acknowledgment which is registered with the Ministry of Law and Human Rights, DJKI.